2016 International Conference on Engineering, Technology and Innovation/Ieee Lnternational Technology Management Conference (IC 2016
DOI: 10.1109/ice/itmc39735.2016.9026129
|View full text |Cite
|
Sign up to set email alerts
|

Elements of installed base information value

Abstract: Installed base information (IBI) is used in industrial service operations, but currently there are challenges with maintaining and utilizing this information to its full potential. The purpose of this paper is to aid in improving the realized value of IBI. We conducted two case studies of IBI collection and utilization with two industrial product-service system suppliers. From this material, we identified four elements contributing to the value of IBI and constructed a framework for managing this value. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As such, even when companies build large databases, they can fail to accurately analyze the collected data. A possible cause is identified by Mahlamäki et al (2016), who state that it is difficult to see the value of installed base information before it is utilized.…”
Section: Collection and Organization Of Installed Base Informationmentioning
confidence: 99%
“…As such, even when companies build large databases, they can fail to accurately analyze the collected data. A possible cause is identified by Mahlamäki et al (2016), who state that it is difficult to see the value of installed base information before it is utilized.…”
Section: Collection and Organization Of Installed Base Informationmentioning
confidence: 99%
“…Kuschel (2009) found that companies struggle to integrate data from RMT into their information systems. Mahlamäki et al (2016) found that companies are not able to form a comprehensive view of the installed base due to restricted interaction between various information systems (e.g. product development or service operations).…”
Section: Rmt and Servitisation: Factors Characterising The Organisatimentioning
confidence: 99%
“…Another practical benefit of having the configuration data is in knowing the service history of each component that makes a product. The potential challenge here is data integration which has already been recognised in the literature (Brax and Jonsson 2009;Kuschel 2009;Mahlamäki et al 2016). Namely, status and structure data are collected by and reside in different systems, developed to support different purposes.…”
Section: Data Collectionmentioning
confidence: 99%